Biological Markers of Training Level among Qualified Greco-Roman Wrestlers - Tonoyan, Khoren; Tarasova, Lyubov; Korzhenevskiy, Alexander (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The article presents the dynamics of biochemical indicators showing the tension of body functional systems in qualified Greco-Roman wrestlers at the pre-competition stage. Biochemical indicators can be regarded as the markers of training level, as a reflection of adaptive changes during performing training loads. AIM: The study aims to examine the adaptive reactions of body internal systems in wrestlers to the load performed at the stage of pre-competition training. METHODS: The methodological basis of the study is the examination of the reaction of body functional systems in wrestlers (n = 24) in response to the load performed at the stage of pre-competition training. The basis of the studied indicators of wrestlers’ organisms is the dynamics of the enzymatic activity (ALT and AST), the activity of creatine phosphokinase, and the balance of anabolic and catabolic processes in the course of a 2-week macrocycle of the pre-competition training. RESULTS: A high level of enzymatic activity (ALT and AST) was noted as the response to shock training load in the first and the second training macrocycles against the background of a negative trend during the entire sports event, which indicates a directed decrease in the heart’s tension muscle, being an indicator of adaptive changes occurring in wrestlers’ body energy. The high variability of AST indicators on the first day and creatine phosphokinase throughout the entire pre-competition training pointed out an individual level of adaptive reactions of the athletes’ bodies in response to the training load taken. CONCLUSIONS: The results of the study have shown notable dynamics in the indicators of the enzymatic activity of AST, creatine phosphokinase, and the hormone cortisol in a series of shock training loads, as the response to adaptive changes in body energy systems, the value of which should be considered during the pre-competition training.